2014
DOI: 10.1111/1475-6773.12147
|View full text |Cite
|
Sign up to set email alerts
|

Patient Loyalty in a Mature IDS Market: Is Population Health Management Worth It?

Abstract: Population health management can be beneficial to the care system making this investment, particularly for patients exhibiting prior continuity in care system choice. The results suggest that co-located primary and specialty services are important in maintaining primary care loyalty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Even the 4-year churn rates were lower than a previous study examining individual physicians, which found that 33% of beneficiaries changed physicians after 1 year. [3][4][5]7,8 One potential explanation for these lower churn rates is CMS prioritizing annual wellness visits (AWVs) in the CPC+ attribution methodology (see the Appendix for the CPC+ attribution methodology, Supplemental Digital Content 1, http:// links.lww.com/MLR/C853). In contrast, AWVs were not prioritized in the attribution methodology used in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the 4-year churn rates were lower than a previous study examining individual physicians, which found that 33% of beneficiaries changed physicians after 1 year. [3][4][5]7,8 One potential explanation for these lower churn rates is CMS prioritizing annual wellness visits (AWVs) in the CPC+ attribution methodology (see the Appendix for the CPC+ attribution methodology, Supplemental Digital Content 1, http:// links.lww.com/MLR/C853). In contrast, AWVs were not prioritized in the attribution methodology used in these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have examined attribution stability for individual practitioners and ACOs, we are the first to assess attribution stability in advanced primary care models. [3][4][5][6][7][8] Because of differences between the attribution methods used in ACOs and advanced primary care models, examining advanced primary care models can help identify which methodological differences are important to attribution stability. We analyze the attribution methodology used in Medicare's largest primary care payment and delivery reform model: Comprehensive Primary Care Plus (CPC+).…”
mentioning
confidence: 99%